An Offline Writer-Independent Signature Verification Method with Robustness Against Scalings and Rotations - Huaroto Pachas, Felix Eduardo (2022)
Descargue el texto completo en el repositorio institucional de la Universidade Federal do Rio Grande do Sul: http://hdl.handle.net/10183/247543